Genomic characterization and antimicrobial susceptibility of dromedary-associated Staphylococcaceae from the Horn of Africa - Akarsu, H.; Liljander, Anne M.; Younan, M.; Brodard, I.; Overesch, G.; Glücks, Ilona; Labroussaa, F.; Kuhnert, P.; Perreten, V.; Monecke, S.; Drexler, J.F.; Corman, V.M.; et al. (American Society for Microbiology, 2022)
Camels are a high value and crucial livestock species in arid and semiarid regions of Africa and gain importance giving the impact of climate change on traditional livestock species. Our current knowledge with respect to Staphylococcaceae infecting camels is very limited compared to that for other livestock species. Better knowledge will foster the development of specific diagnostic assays, guide promising antimicrobial treatment options, and inform about potential zoonotic risks.